Degree of Practicing Educational Supervisors in Zarqa First Education Zone of The Concept of Electronic Supervision from Their Point of View - Aledamat, Mohammad Hamed (Journal of Educational and Psychological Sciences, 2020)
The study aimed to identify the degree of exercise of educational supervisors in the Directorate of the first Zarqa education for electronic supervision from their point of view, and to identify the impact of sex, educational qualification, and area of ​​specialization, and experience in this, and the study used the descriptive survey method, and the tool was a questionnaire, distributed The results of the study showed that the degree of educational supervisors in Zarqa First Educational Directorate for the concept of electronic supervision of the tool as a whole; obtained an average of (3.55 out of 5) with a grade of (medium). ), And p At the level of the axes; the reality of the practice of electronic supervision, the highest average (3.95), with a rating (high) followed by the axis of the requirements of electronic supervision with an average (3.61), and thirdly, the importance of electronic supervision with an average (3.50), and finally the axis of obstacles to the use of electronic supervision with an average (The results showed that there are statistically significant differences due to the effect of sex in the field of the practice of electronic supervision and in favor of males, and the absence of statistically significant differences attributed to the other variables. In light of the results, the study recommended a set of recommendations, the most important of which are: Training workshops for educational supervisors on how to employ computer technologies in educational supervision and benefit from the services provided by the Internet and free sites such as Google Drive and others.
Keywords: Degree of exercise; Educational Supervisor; Electronic Supervision; Zarqa First Education Zone